The Level of Remuneration and Turnover Intention of Public Secondary School Teachers in Meru County: A Mixed Method Study - Ekabu, Peter Kalunge (European Scientific Journal, ESJ, 2019)
This paper focuses on establishing the relationship between the level of remuneration and turnover intentions of public secondary school teachers in Meru County. The study used a descriptive survey design with both quantitative and qualitative approaches in data collection and analysis. A total of 518 respondents were involved in the study which included secondary school teachers (503) and principals (15). The level of remuneration was examined to determine their relationships with the dependent variable, turnover intentions. Data obtained from questionnaires were analyzed quantitatively using SPSS version 21. Hypothesis was tested using Pearson product-moment correlation coefficient and Chi-square goodness of fit at 95%, p<0.05. The result from product-moment correlation indicated that the independent variable, level of remuneration (r=-387, p<0.001), has a negative and an inverse relationship with the dependent variable, turnover intention. Chi-square analysis corroborated the results of Pearson correlation by showing a significant relationship between the level of remuneration and turnover intentions of secondary school teachers in Meru County. The results conclude that teachers’ motivation in secondary schools in Meru County is low. Schools are also staffed with teachers with poor morale and low levels of commitment to their jobs due to inadequate and low remuneration. This has led to high turnover intentions. The study recommends that the Teachers Service Commission should consider issues of remuneration especially enhancing the current allowances and introducing new ones in motivating and reducing turnover intentions. Hence, this will lead to increased retention in teaching service.